2017
DOI: 10.1111/jav.01424
|View full text |Cite
|
Sign up to set email alerts
|

Do environmental conditions experienced in early life affect recruitment age and performance at first breeding in common goldeneye females?

Abstract: Environmental conditions experienced early in life may have long‐term impacts on life history traits and reproductive performance. We investigated whether ambient temperature experienced during the first two to four weeks of life and weather severity during the first two winters affected recruitment age and relative timing of breeding in the year of recruitment in female common goldeneyes Bucephala clangula. Our sample consisted of 141 female recruits hatched in a study population in central Finland between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It has been found that the relative timing of first reproduction is affected by winter severity, recruits (first-time breeders) breeding later relative to the population mean after cold winters (Pöysä et al 2017). One possible explanation for this is that their weaker physiological condition prevented earlier nest initiation after harsh winters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the relative timing of first reproduction is affected by winter severity, recruits (first-time breeders) breeding later relative to the population mean after cold winters (Pöysä et al 2017). One possible explanation for this is that their weaker physiological condition prevented earlier nest initiation after harsh winters.…”
Section: Discussionmentioning
confidence: 99%
“…Here, I tested the above population‐level predictions, while simultaneously taking into account possible impacts of other potentially important factors on the rate of parasitic laying, including conditions during the previous winter (harsh weather in the wintering area may affect female condition, breeding propensity, and breeding performance; Fredga and Dow 1983, Lehikoinen et al 2006, Pöysä et al 2017), population density (population or nest density may affect opportunities for parasitic laying; Rohwer and Freeman 1989, Lyon 2003) and nest predation rate in the same year (parasitic laying may be a response to nest loss in the laying stage in the same season; Yom‐Tov 1980, Eadie et al 1988, Lyon and Eadie 2008). In addition, using annual data of the numbers of nesting attempts and potential nesting females, I assessed the occurrence of non‐nesting females and the pure parasite tactic in the population.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, other researchers reported locally measured conditions were more informative of survival than large-scale climate indices (Szostek and Becker 2015). Alternatively, it may be that lesser scaup are robust to variation in winter weather, as seems to be the case in the limited studies of over-winter survival in some duck species (Bergan and Smith 1993, Dugger et al 1994, Pöysä et al 2017.…”
Section: Discussionmentioning
confidence: 99%